Recent applications of paper‐based point‐of‐care devices for biomarker detection. Issue 5 (24th October 2019) - Suntornsuk, Worapot; Suntornsuk, Leena
Abstract: Detection of biomarkers is essential for diagnosis and prognosis of diseases for healthcare teams to provide timely appropriate treatments. Reliable, inexpensive, and sensitive devices are desirable to serve this purpose. Paper‐based analytical devices (PADs) have gained enormous attention during the past decade as point‐of‐care devices for biomarker detection due to their simplicity, portability, and biocompatibility. Importantly, the devices highly comply with the WHO "ASSURED" concept (i.e. Affordable, Sensitive, Specific, User‐friendly, Rapid and Robust, Equipment free, and Deliverable to end‐users). Thus, PADs could be sustainably alternative tools for biomarker detection, especially in resources‐constraint areas where budget, skillful operators, and health infrastructure are limited. First, this review introduces overviews of biomarkers, their detection and brief history of PADs. Second, description of common fabrication and detection techniques in PADs are provided. Then, it highlights recent state of the art technologies and applications of PADs for various biomarker detection published during 2018 to May 2019. Applications for tumor marker, cardiac and coronary heath disease, and metabolic disorder biomarker detection are tabulated and selected examples are described in details. Finally, it discusses the current challenges, advances, and novel applications of PADs. The review would be valuable for healthcare workers using PADs as cost‐effective point‐of‐care devices for biomarker detection and for researchers working on future developments of the devices.